IMPROVING CHILDREN'S LANGUAGE SKILLS THROUGH THE MEDIA ILLUSTRATED STORY BOOK - Wulan Sari (IKIP Siliwangi Bandung, 2020)
Abstract Early childhood education has a large role in efforts to develop children's language skills. The problem that often occurs in language development at the level of early childhood education is that children are still experiencing difficulties in expressing language correctly. So it is necessary to have a strategy in managing and implementing appropriate learning media to be able to improve children's language activities. The purpose of this research is to find out the process of applying picture book media strategies as an effort to improve children's language skills. This research uses a descriptive method with a qualitative approach. Data collection techniques through interviews, observation and documentation study. Subjects in this study were 2 teachers, and students aged 4-5 years as many as 20 children in Kober Ya Ibna, Cibabat Sub-District, Cimahi Utara District, Cimahi City. The results showed that; (1) strategies in improving children's language skills through the media picture books begin with the planning stage, (2) the implementation of the effectiveness of language learning activities through the picture book media can improve children's ability in language, (3) the difficulties encountered in the learning process includes the limitations of story books and other infrastructure that can be handled well so that they don't interfere with the learning process. Media illustrated story books through the method of storytelling conducted by the teacher has an important role in improving language skills in children. Because of the importance of this learning strategy, it is essential to sustainable development and develop it. Keywords: Early childhood; Language skill; The media of picture books